PENGARUH KINERJA KEUANGAN DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI TAHUN 2010-2014) - Budi Tri Rahardjo, Ak., M.Ak., CA; Ria Murdani (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
This study was conducted to determine how much influence partially or simultaneously between financial performance and disclosure of corporate social responsibility to corporate value in state-owned companies listed on the Stock Exchange in 2010-2014. In this study conducted random sampling method with a selected number of samples as many as 80 state-owned companies on the Stock Exchange during the five years 2010-2014. Data were analyzed using multiple regression analysis techniques are processing using software SPSS version 20.0. The results showed that the variables of financial performance and corporate social responsibility disclosures partially show a significant effect on the variable value of the company is to the t value respectively 7.172 and 2.113. Simultaneous testing also showed a significant effect on all of the independent variable on the dependent variable, meaning that together the financial performance and corporate social responsibility disclosures affect the value of the company is the calculated F value of 35.721.